Adherent cell depletion promotes the expansion of renal cell carcinoma infiltrating T cells with optimal characteristics for adoptive transfer. Issue 2 (9th October 2020) - Braun, Mitchell W; Abdelhakim, Haitham; Li, Meizhang; Hyter, Stephen; Pessetto, Ziyan; Koestler, Devin C; Pathak, Harsh B; Dunavin, Neil; Godwin, Andrew K
Abstract : Background: Tumor-infiltrating lymphocyte (TIL) therapy is a personalized cancer treatment which involves generating ex vivo cultures of tumor-reactive T cells from surgically resected tumors and administering the expanded TILs as a therapeutic infusion. Phase 1 of many TIL production protocols use aldesleukin (IL-2) alone to establish TIL cultures (termed "PreREP" (Pre-Rapid Expansion Protocol)); however, this fails to consistently produce TIL cultures from renal cell carcinoma (RCC) in a timely manner. Adding mitogenic stimulation via anti-CD3/anti-CD28 beads along with IL-2 to the fresh tumor digest (FTD) during TIL generation (termed "FTD+ beads") increases successful TIL culture rates; however, T cells produced by this method may be suboptimal for adoptive transfer. We hypothesize that adherent cell depletion (ACD) before TIL expansion will produce a superior TIL product by removing the immunosuppressive signals originating from adherent tumor and stromal cells. Here we investigate if "panning, " a technique for ACD prior to TIL expansion, will impact the phenotype, functionality and/or clonality of ex vivo expanded RCC TILs. Methods: Tumor specimens from 55 patients who underwent radical or partial nephrectomy at the University of Kansas Medical Center (KUMC) were used to develop the panning method and an additional 19 specimens were used to validate the protocol. Next-generation sequencing, immunohistochemistry/immunocytochemistry and flow cytometry were used during method development. The phenotype, functionality and clonality of autologous TILs generated in parallel by panning, PreREP, and FTD+ beads were assessed by flow cytometry, in vitro co-culture assays, and TCRB CDR3 sequencing. Results: TIL cultures were successfully generated using the panning protocol from 15/16 clear cell, 0/1 chromophobe, and 0/2 papillary RCC samples. Significantly fewer regulatory (CD4+/CD25+/FOXP3+) (p=0.049, p=0.005), tissue-resident memory (CD8+/CD103+) (p=0.027, p=0.009), PD-1+/TIM-3+ double-positive (p=0.009, p=0.011) and TIGIT+ T cells (p=0.049, p=0.026) are generated by panning relative to PreREP and FTD+ beads respectively. Critically, a subset of TILs generated by panning were able to degranulate and/or produce interferon gamma in response to autologous tumor cells and the average tumor-reactive TIL yield was greatest when using the panning protocol. Conclusions: Removing immunosuppressive adherent cells within an RCC digest prior to TIL expansion allow for the rapid production of tumor-reactive T cells with optimal characteristics for adoptive transfer.